Utility of a novel activity monitor assessing physical activities and sleep quality in cats - Yamazaki, Atsushi; Edamura, Kazuya; Tanegashima, Koji; Tomo, Yuma; Yamamoto, Makoto; Hirao, Hidehiro; Seki, Mamiko; Asano, Kazushi (PLOS ONE, 2020)
Osteoarthritis in cats is more prevalent because cats are living longer with advancement in veterinary medicine. Objective evaluation of behavioral changes in cats with osteoarthritis can facilitate an early diagnosis. The objective of this study was to investigate the utility of a novel activity monitor for analyzing physical activities and sleep quality in cats. First, a novel activity monitor (Plus Cycle®; JARMeC, Kanagawa, Japan), with a built-in three-directional accelerometer and an air pressure sensor specifically designed for cats, was compared to a human activity monitor (Actical®; Philips Respironics, OR, USA) previously used in cats (n = 10). Second, the validity of the measurement accuracy of the amount of physical activity, the number of vibrations, the number of jumps, and the resting and sleeping time was evaluated using Plus Cycle® in healthy cats (n = 6). Finally, the effects of gender and age of cats and time of day on the amount of physical activity, the number of vibrations, the number of jumps, and the resting and sleeping time were investigated in client-owned cats (n = 61). There were strong correlations between Plus Cycle® and Actical® in total activity (p < 0.05) and activity intensity (p < 0.05). When the physical activities were measured using Plus Cycle® in healthy cats, those data were quantified with high accuracy. In addition, it was also found to be very accurate in discriminating the resting and sleeping conditions of cats. In client-owned cats, there were no significant differences with respect to gender in any measured traits. The amount of physical activity and the number of jumps significantly decreased with the age of the cat. In contrast, the resting and sleeping times significantly increased with the age of the cat. In conclusion, Plus Cycle® can accurately and objectively assess physical activities and sleep quality with age of the cat, suggesting that this novel activity monitor can be used to manage the feline musculoskeletal health.